Analysis of vehicle acceleration and cornering performance with the Direction Sensitive Locking Differential (DSLD) - Carlsson, Mattias; Tunlid, Markus (My University, 2011)
The purpose of this Master's Thesis was to, through simulations, evaluate the advantages of the Direction Sensitive Locking Differential, DSLD, in various driving situations. The purpose was also to simulate situations that indicates possible risks of a mechanically locked differential. A vehicle model with chassis and drivetrain and a driver model that can follow a predefined path and given speed curves were developed in MATLAB/Simulink. Then a number of driving situations were simulated in MATLAB/Simulink showing different effects of the DSLD and how it affected the performance and maneuverability of the vehicle. The results of the simulations show that the DSLD preferably is positioned on the front axle in a four wheel driven vehicle and the DSLD makes the largest dierence in cornering ability and acceleration in a front wheel driven vehicle. The DSLD will both contribute to produce more power/grip/yaw when accelerating in corners as well as it will reduce yaw motion when in oversteered situations, such as the Sine with Dwell. No problems has been shown with the DSLD remaining locked in the a prefered direction. It has followed the quickest reactions of the driver and the fastest movements of the vehicle without any problems. The worst case simulation showed that even when the DSLD was forced to lock in the wrong direction, it wasn't any notable loss in cornering ability when unlocking it with a short brake activation. What needs to be developed further is the interactions and cooperation between the DSLD and the brake, chassis and powertrain/engine control and the other systems that already exists in a vehicle. By developing these interactions the maximum effect of the differential can be achieved and the risk that the systems will work against each other will be reduced. The main thing that is needed is a signal from the DSLD to the other systems with the information whether and how the differential is locked and then the other systems will have to take that into account.
Keywords: Transport; Teknisk mekanik; Transport; Applied Mechanics